POLA ASUH ORANG TUA YANG MEMILIKI ANAK PUTUS SEKOLAH DI KAMPUNG PABEAN KELURAHAN PADUKUHAN KRATON LOR (PARENTS’ PARENTING TOWARD DROP OUT CHILDREN IN KAMPUNG PABEAN PEKALONGAN) - Permanasari, Pradnya; Panuntun, Ida Ayu; Fitri, Amalia (BAPPEDA Kota Pekalongan, 2016)
BUILDING LEARNERS’ CHARACTER WHICH CONSISTS OF SOFT SKILL AND HARD SKILL IS NOT EASY. ITS PROCESS TAKES A LONG TIME AND THE UNDERSTANDING OF PARENTING IS ONE OF THE WAYS. PARENTING IN KAMPUNG PABEAN WAS STILL BEING A BIG QUESTION. THE IMPORTANCE OF THE TIME TO FULFILL FAMILY’S NEED WAS THE MAIN REASON TO ANSWER THAT. LEARNERS’ EDUCATION LEVEL AND THE TOTAL OF DROP OUT STUDENTS WAS ONE OF THE EFFECTS OF PARENTING ROLE IN THE FAMILY. THE OBJECTIVE OF THE RESEARCH WAS TO DESCRIBE HOW THE PARENTS’ PARENTING TOWARD DROP OUT CHILDREN IN KAMPUNG PABEAN KELURAHAN PADUKUHAN KRATON LOR. THIS RESEARCH USED DESCRIPTIVE QUALITATIVE DESIGN. THE SUBJECT OF THIS RESEARCH WAS 41 PARENTS WHO HAD DROP OUT CHILDREN IN THE AGE OF 12-18 YEAR. THE RESULT OF THE RESEARCH WAS FROM 41 PARENTS WHO HAD DROP OUT CHILDREN IN THE AGE OF 12 TO 18 YEARS OLD, THERE WERE 31 PARENTS APPLIED PERMISSIVE PARENTING AND 10 OF THEM APPLIED DEMOCRATIC ONE. THE RESEARCHERS SUGGEST THAT THE FINDING OF THE RESEARCH CAN BE USED TO IMPROVE THE PARENTS’ UNDERSTANDING ABOUT PARENTING, SO THEY CAN GIVE MORE MOTIVATION FOR THEIR CHILDREN TO HAVE A HIGHER EDUCATION LEVEL.